Facebook as a Platform for Using English Language Skills among the Indian Youth (Journal of NELTA, 2014)
Today Facebook undoubtedly is one of the preferred Social Networking Site (SNS) platforms used by millions of people worldwide. Facebook users often use its unique creative applications and in the process also make use of smart abbreviations and ingenious expressions for everyday interactions. It is quite apparent that in such type of electronic communication and user-oriented media it is imperative to understand casual written English, which often does not conform to the rules of spelling, grammar and punctuation. It is generally being observed that repeated Facebook usage has the potential of providing the user new expressions of language through its various available features. Within the framework of such observations, this paper discusses the impact of Facebook on English language use of the youth in India. The study employed a survey design among young professionals, home-makers and graduate students, to fulfil the objectives. The results revealed a few surprising particulars. The key findings show that: i. as perceived by the youngsters themselves, by ‘facebooking’ there is mark deterioration in their English writing skills, ii. not many changes are seen in their day-to-day English language use despite their remaining abreast of the latest colloquial and casual English, and iii. Facebook is used by young people mainly for recreation purpose and any improvement that is seen in their English language skills is purely incidental. DOI: http://dx.doi.org/10.3126/nelta.v18i1-2.10326   Journal of NELTA, Vol 18 No. 1-2, December 2013; 1-17